2014
DOI: 10.1373/clinchem.2013.211953
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Proteolytic Products of Carboxypeptidase N for Early Detection of Breast Cancer

Abstract: Background Carboxypeptidase N (CPN) plays an important role in regulating vasoactive peptide hormones, growth factors, and cytokines by specifically cleaving their C-terminal basic residues. Herein we demonstrated that the circulating peptides specifically cleaved by CPN in the tumor microenvironment can indeed be stage-specific indicators of breast cancer. Methods The activity of CPN was evaluated using an ex-vivo peptide cleavage assay, in which synthesized C3f peptide (His6-C3f_S1304-R1320-His6) is incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 37 publications
0
29
1
Order By: Relevance
“…Effective real-time extraction from biological samples and subsequent ionization at relatively high efficiency have been well demonstrated with a variety of ambient ionization methods [45,66]. The circulating proteolytic products in biofluids [82] might also become suitable biomarkers for screening by the small MS systems. The spray-based methods, in comparison with plasma-based ones, might be of an advantage for the ease of extraction and ionization of biomolecules.…”
Section: Discussionmentioning
confidence: 99%
“…Effective real-time extraction from biological samples and subsequent ionization at relatively high efficiency have been well demonstrated with a variety of ambient ionization methods [45,66]. The circulating proteolytic products in biofluids [82] might also become suitable biomarkers for screening by the small MS systems. The spray-based methods, in comparison with plasma-based ones, might be of an advantage for the ease of extraction and ionization of biomolecules.…”
Section: Discussionmentioning
confidence: 99%
“…Interesting, the C3f fragment (m/z 1098.537) posses an opposite trend with respect its precursor peptide at m/z 2021.106 and this could correspond to differences in cancer exoproteases activity. Cancer proteases have been recently recognised as possible biomarker source, since they can generate specific fragmentation patterns (Villanueva et al, ; Gianazza et al, ; Li et al, ) from common precursor proteins. Moreover, a potential implication of higher levels of C3 circulating in pCRT resistant CRC patients should be considered, since similar results have been obtained in esophageal cancer patients underwent neo‐adjuvant chemoradiation (Maher et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Carboxypeptidase N (CPN)-associated peptide profiles in mouse and human blood samples correspond with those found in the interstitial fluid of mouse breast tumors or with CPN expression in normal breast tissue or breast tumor biopsies of women with various stage breast tumors. 3 We also found that in mice carrying ovarian tumors, serum levels of two complement C3fderived peptides were primarily generated by tumor-resident matrix metalloproteases 9 (MMP-9) activity, which decreased in response to positive responses to therapeutic siRNA intervention.…”
mentioning
confidence: 86%